Treatment with novel topoisomerase inhibitors in Ewing sarcoma models reveals heterogeneity of tumor response - Lee, Unsun; Szabova, Ludmila; Collins, Victor J.; Gordon, Melanie; Johnson, Kristine; Householder, Deborah; Jorgensen, Stephanie; Lu, Lucy; Bassel, Laura; Elloumi, Fathi; Peer, Cody J.; Nelson, Ariana E.; et al. (Frontiers in Cell and Developmental Biology, 2024)
The topoisomerase 1 (TOP1) inhibitor irinotecan is a standard-of-care agent for relapsed Ewing sarcoma (EWS), but its efficacy is limited by chemical instability, rapid clearance and reversibility, and dose-limiting toxicities, such as diarrhea. Indenoisoquinolines (IIQs) represent a new class of clinical TOP1 inhibitors designed to address these limitations. In this study, we evaluated the preclinical efficacy of three IIQs (LMP400, LMP744, and LMP776) in relevant models of EWS. We show that IIQs potently inhibit the proliferation of EWS cells in-vitro, inducing complete cell growth inhibition at nanomolar concentrations via induction of DNA damage and apoptotic cell death. We characterized the pharmacokinetics of IIQs in orthotopic xenograft models of EWS, optimized the dosing regimen through tolerability studies, and tested the efficacy of IIQs in a panel of six molecularly heterogeneous EWS patient-derived xenograft (PDX) models. LMP400 treatment induced ≥30% tumor regression in two of six PDX models, with more durable regression compared to irinotecan treatment in one of these models. For each PDX, we conducted whole genome and RNA sequencing, and methylation analysis. These data, along with pharmacogenomic data on IIQs in sarcoma cell lines, are available at a new interactive public website: https://discover.nci.nih.gov/rsconnect/EwingSarcomaMinerCDB/. RNA sequencing of PDX models identified a candidate predictive biomarker gene signature for LMP400 response. Our findings suggest that IIQs may be promising new agents for a subset of EWS patients.